Study of the Impact of High Temperature of Cooling Water and Hydrocarbon Waste Discharged from Musayyib Thermal Station to the Euphrates River Using Remote Sensing Stations - Aws Ismael, Shams; Abdul Majeed, Omar; Akram, Evon; Aqeel, Ahmed; Mohammed, Salam (Al-Nahrain Journal of Science, 2024)
The spread of industrial activities, especially electrical power generation stations on the banks of rivers, increases the pollution of the surrounding water environment as a result of the release of industrial water that is not treated adequately. Among these stations is the Al-Musayyib Thermal Power Station. The research focused on studying the quality of the water entering and leaving the station by installing two sensing stations. Remote monitoring of the Euphrates River, as the station contains several sensors, including measuring acidity, dissolved oxygen, turbidity, and the amount of total salts, in addition to a sensor for measuring refined fuel. These results are collected around the clock at a central station, where the results showed a decrease in the level of dissolved oxygen ranging between (3.5-5) RSD% 0.1-0.2 as well as an increase in The temperature of the excreted water ranging between from (30Cº-33Cº) RSD% 0.1-0.2, both of which negatively affect the environmental life of living organisms, as well as the appearance of a high percentage of pollutants resulting from refined fuel, ranging between (2.1-8.1) ppm, The findings will contribute to improving the efficiency of treatment plants to suit the environment surrounding the river, In order to preserve the water environment, it is necessary to place oil dispensers in the treatment units, as well as work to reduce the temperatures of the cooling water, which are at temperatures higher than the medical grades coming out of the station.